Efeitos endócrinos e comportamentais do estradiol em Zebrafish - Moraes, Andreia Benetti (2020)
The consumption of estrogenic hormones by human population has increased in recent years and, consequently, its presence in surface, groundwater and effluents also grows. In addition, these hormones present in the environment exert endocrine disruption effects, triggering behavioral and physiological changes. Estradiol (17β-estradiol, E2) is an estrogen that regulates cognitive, social and affective behaviors. However, the complexity of the effects of E2 on the central nervous system (CNS), including its activity in males, is little known. Zebrafish is a model organism widely used in biomedicine, including neurobehavioral and neuropharmacological research, as it demonstrates a high genetic and physiological homology compared to mammals. Zebrafish also have highly conserved mammalian estrogen receptors and synthesis and inactivation enzymes. The present study evaluated the effects of 24-hour exposure to E2 (20 μg / L) on behavioral and endocrine responses in adult male zebrafish. Two experiments were carried out: in experiment 1, shoaling behavior (n = 8 per group) and social interaction (n = 32) and; in experiment 2, anxiety behavior (n = 12) and cortisol levels were evaluated. E2 exerted a pro-social effect in the social preference test and reduced cortisol levels, increased exploration in the new tank test and increased the size of the shoal in the shoaling test, indicative of the anxiolytic profile. Supporting the growing evidence on the role of E2 in behavioral regulation in humans and rodents, the prosocial and anxiolytic effects observed from acute exposure to E2 in male zebrafish reinforce the use of this aquatic organism in studies on hormone-mediated social and affective behaviors steroids.